Public Administration in Conflict Affected Countries
XXI, 451 p. 21 illus., 5 illus. in color.
Keywords: This book highlights the main factors determining the quality of public administration in conflict affected countries; and assesses to what extent the conflict determines and impacts on the performance of public administration in affected countries. The main value added by this book is confirming the general expectation that there is no direct and universal link between the conflict and public administration performance (and vice-versa). One may need to argue that each country situation differs and specific factors of internal and external environments determine the trends of public administration performance in conflict affected countries. To achieve the overarching goal of the book, sixteen country studies were developed from all relevant continents - America, Africa, Asia and Europe: Bangladesh, Colombia, Croatia, Egypt, Georgia, Iraq, Kosovo, Nigeria, Palestine, Paraguay, Philippines, Serbia, South Africa, Uganda, Ukraine, and Venezuela. Purshottama Sivanarain Reddy is Senior Professor and Subnational Governance Specialist at the University of Kwazulu Natal, South Africa. Juraj Nemec is Professor at the Masaryk University in Brno, Czech Republic, and at the Matej Bel University in Banska Bystrica, Slovakia. .